The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c8cc04826f
|View full text |Cite
|
Sign up to set email alerts
|

Using hyperpolarised NMR and DFT to rationalise the unexpected hydrogenation of quinazoline to 3,4-dihydroquinazoline

Abstract: Hyperpolarised NMR allows the tracking of the DFT-rationalised outer sphere hydrogenation of quinazoline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…An iridium centred catalyst is typically employed to propagate polarisation, via J‐coupling, between the para hydrogen derived hydrides and the spin‐1/2 nuclei of the analyte molecule being polarised . The pre‐catalyst, [Ir(IMes)(COD)Cl] (IMes=1,3‐ bis (2,4,6‐trimethylphenyl)imidazole‐2‐ylidene, COD=cyclooctadiene) has been shown to be an excellent catalyst, following activation, in this regard for a number of substrates such as nicotinamide, quinazoline, and niacin . Manipulation of the spin‐reservoir of the substrate, such as deuteration, has been shown to be an effective route by which polarization can be maximized.…”
Section: Introductionmentioning
confidence: 99%
“…An iridium centred catalyst is typically employed to propagate polarisation, via J‐coupling, between the para hydrogen derived hydrides and the spin‐1/2 nuclei of the analyte molecule being polarised . The pre‐catalyst, [Ir(IMes)(COD)Cl] (IMes=1,3‐ bis (2,4,6‐trimethylphenyl)imidazole‐2‐ylidene, COD=cyclooctadiene) has been shown to be an excellent catalyst, following activation, in this regard for a number of substrates such as nicotinamide, quinazoline, and niacin . Manipulation of the spin‐reservoir of the substrate, such as deuteration, has been shown to be an effective route by which polarization can be maximized.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of 1, 2 and 3 is 37 confirmed by the data presented in the main text. 38 39 2 Pre-catalyst [IrCl(IMes)(COD)] (11 mM) was dissolved in 600 µL of pyridine-d5, yielding a 66 light to dark yellow solution. The solution was exposed to hydrogen in a pressure tube at 10 bar 67 for 2 hours, until it turned into a light yellow liquid.…”
mentioning
confidence: 99%
“…In a previous study 32 , weak peaks with similar chemical shifts were observed at low temperature and were assigned to the solvent-binding complex [Ir(IMes)(Py)2(CD3OD)(H)2] + Cl -. A more recent study 39 , however, reported similar chemical shift values (-22.77 ppm and −23.78 ppm) for the complex…”
mentioning
confidence: 52%